The Maccera Manurung Tradition in the Labuku Village Community: A Perspective of Maslahah - Hidayat, Rian; Mustafa, Zulhas'ari; Ahmad, La Ode Ismail (Al Ahkam, 2024)
This study examines how the Maccera Manurung tradition in Labuku Village combines cultural practices with Islamic principles, focusing on its values. The primary goal of this study is to uncover and analyze the spiritual, social, and cultural values, specifically examining the impact on social cohesion and community structure. This study uses field research with descriptive qualitative models, considering normative, historical, phenomenological, and sociological perspectives. The findings reveal that Maccera Manurung functions as a mechanism to achieve social and spiritual well-being for the community by integrating Islamic values with local culture. This tradition maintains a balance between worldly and spiritual needs through rituals such as animal sacrifices following Islamic guidelines, visiting graves, and engaging in prayers. The people of Labuku preserve their cultural identity by participating in annual rituals, maintaining traditional customs, and upholding ancestral practices, which strengthen social solidarity and reinforce spiritual and moral values. Maccera Manurung emphasizes simplicity, self-control, and responsibility, serving as a means to draw closer to Allah and enhance the spiritual character of the community